2022
DOI: 10.1038/s41598-022-15382-5
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome assembly and comprehensive assessment provide insight into fruiting body formation of Sparassis latifolia

Abstract: The genes associated with fruiting body formation of Sparasis latifolia are valuable for improving mushroom breeding. To investigate this process, 4.8 × 108 RNA-Seq reads were acquired from three stages: hyphal knot (SM), primordium (SP), and primordium differentiation (SPD). The de novo assembly generated a total of 48,549 unigenes, of which 71.53% (34,728) unigenes could be annotated by at least one of the KEGG (Kyoto Encyclopedia of Genes and Genomes), GO (Gene Ontology), and KOG (Eukaryotic Orthologous Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Our transcriptome analysis and gene expression profiles in comparison among groups revealed that the expression levels of multiple genes in these signal pathways were significantly down-regulated by excessive oxalic acid, thereby impairing the expression of these pathways and inhibiting the saprophytic growth of S. latifolia mycelia. Moreover, our previous study also revealed that the MAPK, PI3K–Akt, and mTOR signaling pathways play important roles in primordium formation and fruiting body development [ 52 ]. Therefore, many down-regulated genes in these signal pathways will seriously restrict the mycelial growth and the fruiting body development of the S. latifolia , leading to the prolongation of the cultivation cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Our transcriptome analysis and gene expression profiles in comparison among groups revealed that the expression levels of multiple genes in these signal pathways were significantly down-regulated by excessive oxalic acid, thereby impairing the expression of these pathways and inhibiting the saprophytic growth of S. latifolia mycelia. Moreover, our previous study also revealed that the MAPK, PI3K–Akt, and mTOR signaling pathways play important roles in primordium formation and fruiting body development [ 52 ]. Therefore, many down-regulated genes in these signal pathways will seriously restrict the mycelial growth and the fruiting body development of the S. latifolia , leading to the prolongation of the cultivation cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Tools for de novo transcriptome assembly such as the Trinity software can make transcriptomic analysis without reference genomes more feasible [ 113 ]. Trinity has been successfully utilized for de novo assemblies of transcriptomes and metatranscriptomes containing signatures from multiple kingdoms [ 114 116 ]. Other tools and methods for separating host and symbiont reads in holobiont systems have been designed that minimize the chimeras that can typically arise from de novo transcriptome analyses [ 117 ].…”
Section: Challenges For Integrative Multi-omics Of the Endohyphal Mic...mentioning
confidence: 99%